Vascular effects on ciliary tissue from endoscopic versus trans-scleral cyclophotocoagulation. Issue 4 (17th March 2006) - Lin, S C; Chen, M J; Lin, M S; Howes, E; Stamper, R L
Abstract : Aim: To determine the acute and chronic vascular effects of endoscopic cyclophotocoagulation (ECP) versus trans-scleral cyclophotocoagulation (TCP) in a rabbit model. Methods: 20 rabbits underwent ECP in one eye and another 20 rabbits had unilateral TCP. Five treated eyes from each group underwent endoscopic fluorescein angiography (EFA) of the treated ciliary processes at each of the following time points: immediate, 1 day, 1 week, and 1 month. Five untreated rabbits were used as controls. The NIH Image software program was used to trace ciliary processes in order to determine their mean intensity, as a measure of their perfusion. Histopathology was also performed on eyes from each time point. Results: Immediately and 1 day after laser, both TCP and ECP eyes demonstrated severely reduced or non-existent blood flow in the areas of treatment. TCP treated processes essentially remained non-perfused at the 1 week and 1 month time points. ECP treated processes showed some reperfusion at 1 week and greater reperfusion by 1 month. Histopathology confirmed the overall greater vascular occlusion seen with TCP. Conclusions: Chronic poor perfusion of the ciliary body after TCP may account, in part, for its efficacy, as well as the significant complications including hypotony and phthisis. Late reperfusion of this region after ECP may provide some insight into the differences in efficacy and complication rates compared to TCP.